The real effects of tax havens - Alstadsӕ Annette ter; Ronald B. Davies; Mathieu Parenti; Farid Toubal (University College Dublin, UCD School of Economics, 2023)
It is common to summarize the impact of tax havens as a shift of tax revenues from high to low-tax jurisdictions. This chapter discusses the economic impact of tax havens that goes beyond a zero-sum transfer of the tax base, what we label real effects. We review the literature and focus on exploring how profit shifting affects employment, investment, and innovation in firms. We consider in turn how real effects shape market structure and their implications in general equilibrium. In conclusion, we propose some potential pathways for future research in terms of methodology and areas that we deem promising for further exploration.
Keywords: H25; H26; F23; 330; Tax Haven; Profit Shifting; Tax Evasion; Real Effects